CORRELATION BETWEEN PRE AND POSTOPERATIVE LEVELS OF GLP-1/GLP-2 AND WEIGHT LOSS AFTER ROUX-EN-Y GASTRIC BYPASS: A PROSPECTIVE STUDY - CAZZO, Everton (Arq Bras Cir Dig, 2016)
BACKGROUND: The role of gut hormones in glucose homeostasis and weight loss achievement and maintenance after bariatric surgery appears to be a key point in the understanding of the beneficial effects observed following these procedures. AIM: To determine whether there is a correlation between the pre and postoperative levels of both GLP-1 and GLP-2 and the excess weight loss after Roux-en-Y gastric bypass (RYGB). METHODS: An exploratory prospective study which enrolled 11 individuals who underwent RYGB and were followed-up for 12 months. GLP-1 and GLP-2 after standard meal tolerance test (MTT) were determined before and after surgery and then correlated with the percentage of excess loss (%EWL). RESULTS: GLP-2 AUC presented a significant postoperative increase (945.3±449.1 vs.1787.9±602.7; p=0.0037); GLP-1 AUC presented a non-significant trend towards increase after RYGB (709.6±320.4 vs. 1026.5±714.3; p=0.3808). Mean %EWL was 66.7±12.2%. There was not any significant correlation between both the pre and postoperative GLP-1 AUCs and GLP-2 AUCs and the %EWL achieved after one year. CONCLUSION: There was no significant correlation between the pre and postoperative levels of the areas under the GLP-1 and GLP-2 curves with the percentage of weight loss reached after one year.